Try NerdPal! Our new app on iOS and Android

# Solve the quadratic equation $-x^2-2x+3=0$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$x=-3,\:x=1$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

$-x^2-2x+3=0$

Specify the solving method

1

Factor the trinomial by $-1$ for an easier handling

$-\left(x^2+2x-3\right)=0$

Learn how to solve quadratic equations problems step by step online.

$-\left(x^2+2x-3\right)=0$

Learn how to solve quadratic equations problems step by step online. Solve the quadratic equation -x^2-2x+3=0. Factor the trinomial by -1 for an easier handling. Factor the trinomial -\left(x^2+2x-3\right) finding two numbers that multiply to form -3 and added form 2. Thus. Factor the trinomial \left(x^2+2x-3\right) finding two numbers that multiply to form -3 and added form 2.

$x=-3,\:x=1$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$-x^2-2x+3=0$